2010
DOI: 10.1093/sleep/33.7.930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paraxanthine and Caffeine on Sleep, Locomotor Activity, and Body Temperature in Orexin/Ataxin-3 Transgenic Narcoleptic Mice

Abstract: Because it is also reported to provide neuroprotection, paraxanthine may be a better wake-promoting agent for hypersomnia associated with neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
1
46
1
1
Order By: Relevance
“…Nonetheless, 42% of our non-low consumer group had detectable levels of caffeine 372 and/or paraxanthine in their saliva. (Paraxanthine is the major metabolite of caffeine in 373 humans and is also psychoactive (Okuro et al 2010).) Perhaps at least some of theseindividuals were in fact consuming sufficient caffeine in their diet to cause them to 375 experience significant adverse effects when caffeine was withdrawn.…”
mentioning
confidence: 99%
“…Nonetheless, 42% of our non-low consumer group had detectable levels of caffeine 372 and/or paraxanthine in their saliva. (Paraxanthine is the major metabolite of caffeine in 373 humans and is also psychoactive (Okuro et al 2010).) Perhaps at least some of theseindividuals were in fact consuming sufficient caffeine in their diet to cause them to 375 experience significant adverse effects when caffeine was withdrawn.…”
mentioning
confidence: 99%
“…Paraxanthine has also less anxiogenic activity and toxicity in rodents than caffeine. [39][40][41] In a recent study, we demonstrated that, in rats, paraxanthine produces a much stronger locomotor-activating effect than caffeine, theophylline or theobromine. The order of efficacies being paraxanthine > caffeine = theophylline > theobromine.…”
Section: Ferré Et Almentioning
confidence: 96%
“…Moreover, administration of caffeine and other stimulants in orexin/ataxin-3 transgenic narcoleptic mice induced an increase in motor activity but the effects on neuropathology remain to be investigated (Okuro et al, 2010) and should be further investigated in MJD models.…”
Section: Neuroprotectionmentioning
confidence: 99%